Overweight and kinesiological aerobic activity for women - Gentiana Beqa; Abdullah Elezi; Gresa Elezi (Kazimierz Wielki University, 2019)
Overweight as a result of the amount of subcutaneous adipose tissue in the body is determined, in addition to its hereditary characteristics , mainly by dietary habits and level of physical activity. Based on the current knowledge that one of the main causes of obesity is inadequate physical activity as the main regulator of energy in the human body, and the purpose of this research is based. The purpose of the research is to determine the impact of planned kinesiological activity ( Kangoo Jumps ) on the reduction of overweight in favor of subcutaneous adipose tissue reduction in females. The population sampled for this research was defined as female populations Mean age = 1995, SD = 4.66. The sample consisted 20 women who for the first time expressed a desire to practice at the "Gettfit Center" fitness center in Pristina. The following anthropometric variables were used to measure body mass and body volume : body weight (ABOWE), circumference of the upper arm (A CIUA) , circumference of the chest (ACICH) , circumference of the upper leg (ACIUL) , circumference of the lower leg (ACILL) and s ubcutaneous fat tissue : upper arm skinfold (AUASK) , subscapular skinfold (ASUSK), abdominal skinfold (AABSK ), upper leg skinfold (AULSK) and lower leg skinfold (ALLSK). The research was conducted during May and June of 2019, meaning it lasted 8 weeks to 3 days a week with one hour of scheduled Kangoo Jumps exercises . For estimating the difference between two dependent groups in arithmetic averages, paired t-test (Paired Sample T-Test) has been applied . We can emphasize that any well-planned physical activity in terms of intensity and extension leads to certain positive changes in the body . The results show that Kangoo Jumps with 128 - 135 bpm high-intensity music 3 times a week for one hour is one of the most effective fitness programs in reducing overweight in favor of reducing subcutaneous body fat mass. Also the results obtained show that t raining aerobic with Kangoo Jumps fitness program has not had the same effect on changes in adipose tissue by r body egjioneve in population gender female hours, this training aerobic shows on a larger effect on reducing subcutaneous adipose tissue in the abdominal region.